Silicon-bridged (1→1)-disaccharides: an umpoled glycomimetic scaffold - Choutka, Jan; Kratochvíl, Michal; Císařová, Ivana; Pohl, Radek; Kaminský, Jakub; Parkan, Kamil (Organic & biomolecular chemistry, 2022)
Modification of the carbohydrate scaffold is an important theme in drug and vaccine discovery. Therefore, the preparation of novel types of glycomimetics is of interest in synthetic carbohydrate chemistry. In this manuscript, we present an early investigation of the synthesis, structure, and conformational behaviour of (1→1)-Si-disaccharides as a novel type of glycomimetics arising from the replacement of interglycosidic oxygen with a dimethyl-, methylpropyl-, or diisopropylsilyl linkage. We accomplished the preparation of this unusual group of umpoled compounds by the reaction of lithiated glycal or 2-oxyglycal units with dialkyldichlorosilanes. We demonstrated the good stability of the "Si-glycosidic" linkage under acidic conditions even at elevated temperatures. Next, we described the conformational landscape of these compounds by the combination of in silico modelling with spectroscopic and crystallographic methods. Finally, we explained the observed conformational flexibility of these compounds by the absence of gauche stabilizing effects that are typically at play in natural carbohydrates.
Keywords: glykosidy; křemík; disacharidy; Disaccharides; Silicon; sacharidy; konformace sacharidů; Carbohydrate Conformation; Oxygen; Glycosides; Carbohydrates; kyslík